Effect of mastitis on the function of milk-derived exosomes: observations from mammary epithelial cells - YING Yitian; YANG Jing; YAN Bingxuan; SHAO Fengjin; TAN Xun (浙江大学学报. 农业与生命科学版, 2020)
The present study was conducted to investigate the effect of mastitic milk-derived exosomes on the viability and innate immune function of bovine mammary epithelial cells (MECs), with the aim to understand the role of exosomes in the pathogenesis of mastitis. Primary MECs were stimulated with heat-killed mastitis causing bacteria (Escherichia coli) for 24 h and subjected to RNA-sequencing and gene ontology (GO) functional classification analysis. It was found that 21 differential expression genes between pathogen-stimulated cells and normal cells were enriched in the cellular component “extracellular vesicular exosome” (GO: 0070062), suggesting that infection may alter the physiological function of exosomes derived from host cells. Based on this finding, MECs were stimulated with the exosomes derived from normal milk (N-exo) and mastitic milk (M-exo), respectively, for 24 h. The cells cultured in the exosome-depleted medium were served as the controls. The cell viability was determined by methyl-thiazol-diphenyltetrazolium (MTT) assay, and the expression of pro-inflammatory cytokines interleukin-8 (IL-8), interleukin-1β (IL-1β) and tumor necrosis factor-α (TNF-α) in the MECs was measured by quantitative real-time PCR (qPCR). The results showed that the exosomes derived from normal milk (N-exo) had no effect on the MEC viability, and those isolated from mastitic milk (M-exo) led to a significant reduction in the cell viability. The exosomes derived from both sources had no effect on the expression of IL-8 and TNF-α. However, the normal milk-derived exosomes significantly induced the expression of IL-1β; in contrast, the exosomes derived from mastitic milk failed to stimulate IL-1β expression. The above results suggest that the exosomes present in milk in the process of udder infection might reduce MEC viability and mediate the formation of a microenvironment favoring the immune escape of pathogens. Thus, it is very likely that exosomes contribute to the pathogenesis of mastitis by helping spread the infection in udder.